PENDAMPINGAN PEMBUATAN KARYA SENI DEKORATIF UNTUK MEMBUAT SUATU KEINDAHAN DALAM BENTUK KARYA SISWA KELAS III MI AR-RAUDHAH KERENG PANGI - Aulia Azizah; Sulistyowati, Sulistyowati; M. Syabrina (Bajang Institute, 2023)
Assistance activities for the community in the framework of Thematic KKN carried out by MBKM students, namely the creation of decorative works of art as well as work programs for MBKM Thematic KKN, FTIK IAIN Palangka Raya. Implementation of this assistance or activity from 18 September 2022 to 25 September 2022. Service for making works Decorative arts are carried out at the MI Ar-Raudhah school which is held on Mondays. This activity is carried out using a gradual method, namely first, preparation, second, introduction, and third, mentoring. Assistance in making decorative works of art has had a positive impact on school-age children at MI Ar-Raudhah in Kampung Palit. This assistance not only has a positive impact on children but also improves children's fine motor skills through decorative drawing activities.